Comparison of long-term outcomes of complete vs. incomplete revascularization in elderly patients (≥75 years) with acute coronary syndrome and multi-vessel disease undergoing percutaneous coronary intervention - Lu, Yu-Ying; Lee, Chen-Hung; Chen, Chun-Chi; Chen, Dong-Yi; Ho, Ming-Yun; Yeh, Jih-Kai; Huang, Yu-Chang; Chang, Chieh-Yu; Wang, Chao-Yung; Chang, Shang-Hung; Hsieh, I-Chang; Hsieh, Ming-Jer (Frontiers in Cardiovascular Medicine, 2023)
Background The optimal revascularization strategy for elderly patients with acute coronary syndrome (ACS) remains uncertain. We evaluated the impact of complete revascularization (CR) vs. incomplete revascularization (IR) in elderly ACS patients with multivessel disease (MVD) undergoing percutaneous coronary intervention (PCI). Methods Using registry data from 2011 to 2019, we conducted a propensity-score matched cohort study. Elderly patients (≥75 years) with ACS and MVD who underwent PCI were divided into CR and IR groups based on angiography during index hospitalization. Major adverse cardiovascular events (MACEs), including all-cause mortality, recurrent non-fatal myocardial infarction, and any revascularization, were assessed at 3-year follow-up. Results Among 1,018 enrolled patients, 496 (48.7%) underwent CR and 522 (51.3%) received IR. After 1:1 propensity-score matching, we analyzed 395 pairs. At 3-year follow-up, CR was significantly associated with lower MACE risk compared to IR (16.7% vs. 25.6%, HR = 0.65, 95% CI: 0.47–0.88, p = 0.006), driven by reduced all-cause mortality. This benefit was consistent across all pre-specified subgroups, particularly in ST segment elevation (STE)-ACS patients. In non-STE (NSTE)-ACS subgroup analysis, CR was also associated with a lower risk of cardiac mortality compared to IR (HR = 0.30, 95% CI: 0.12–0.75, p = 0.01). Conclusion In elderly ACS patients with MVD undergoing PCI, CR demonstrates superior long-term outcomes compared to IR, irrespective of STE- or NSTE-ACS presentation.